Data Atlas for Climate-Smart Agriculture in Kenya - Lamanna, Christine; Steward, Peter R.; Kamau, Hannah N.; Nowak, Andreea C.; Rosenstock, Todd S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Thousands of studies have been published on agricultural innovations in Africa, but those data are generally difficult to access. To make those data accessible, we conducted a systematic review of the impact of more than 100 potential CSA practices on over 50 indicators of productivity, resilience and mitigation in Africa (Rosenstock et al. 2015). The result is a powerful database combining information from more than 1700 studies of CSA in Africa.